iNOS inhibitors: Benzimidazole-coumarin derivatives to combat inflammation - Minhas, Richa; Bansal, Yogita (European Journal of Chemistry, 2022)
Inducible nitric oxide synthase (iNOS) plays an important role in the inflammatory processes via accelerating the production of nitric oxide (NO). The efforts to develop small molecules as selective inhibitors of iNOS are being reported across the globe. The current study explores varied benzimidazole-coumarin derivatives as anti-iNOS agents. Literature survey suggests 2-aminobenzimidazole, coumarin nucleus, and 4-atom linker as important structural components for iNOS inhibition. Target compounds were designed and synthesized by coupling 2-aminobenzimidazole with (un)substituted coumarin through different linkers. These were docked in iNOS (1QW4) and nNOS (1QW6) targets to ascertain their iNOS selectivity, and evaluated for NO and iNOS inhibitory activities in vitro. The most active inhibitors were subsequently evaluated for acute toxicity and anti-inflammatory activity using carrageenan-induced rat paw edema model in vivo. All compounds possessed moderate to good NO and iNOS inhibitory activities. Compounds 14a, 14b, 14d, and 14e were the most potent inhibitors in vitro. These were found to significantly reduce the inflammation. Compounds 14d and 14e have been identified as the most potent iNOS inhibitors to combat inflammation. These derivatives may serve as potential compounds as such against iNOS, or as leads for the development of novel anti-iNOS agents.